Inmunoglobulin G levels in saliva as biological marker in periodontal disease - Bravo-castagnola, Francis (2008)
This study evaluated the concentration of immunoglobulin (IgG) in saliva and its role as a biological marker in periodontal disease. For this study, 50 healthy people and 40 patients with periodontal disease were included as control and study group respectively. The study group was divided in gingivitis and periodontitis subgroups with 20 patients each. The clinical examination evaluated, dental plaque,probing bleeding and probing depth before and after the first phase of treatment. It was taken samples of saliva to determine the IgG concentration through spectrophotometric analysis of its absorbance, in both moments. We found, that the greater the progression of periodontal disease, the most elevated IgG level, showing statistical significant differences between healthy group and gingivitis and periodontitis groups. After treatment, gingivitis group scores decreased until they reached normal rates. The periodontitis group scores, decreased, but not to levels of healthy group. IgG level variations was strongly related to probing depth diagnostic parameter than the other two. We concluded that, IgG levels in total saliva are important biological markers for evaluating periodontal disease’s presence, progression, treatment and effectiveness.